Ultrasound versus Chest X-ray for Confirmation of Central Venous Catheter Tip Position: A comparative study. - Mandal, Lokendra Narayan; Bhattarai, Amit Sharma; Parajuli, Bashu Dev; Acharya, Subhash Prasad; Shrestha, Anil (Journal of Institute of Medicine Nepal, 2025)
Introduction Malposition of central venous catheter (CVC) tip is common after central vein cannulation. Chest radiography is the standard method for confirmation, but ultrasound is gaining popularity for bedside localization, placement confirmation, and complication detection. CVC insertion is frequently performed for various medical purposes. While both chest radiography and ultrasound are used to confirm tip position, ultrasound is radiation-free and faster. Real-time ultrasound during insertion reduces attemptsto catheterisation and complications like pneumothorax. However, radiographic confirmation remains the gold standard. This study aimed to evaluate the accuracy and speed of ultrasound compared to chest X-ray for confirming CVC tip position. Methods A total of 109 patients (aged 15–65 years) who underwent CVC insertion via the right internal jugular vein were enrolled. Written informed consent was obtained from patients or family members. Sonographic confirmation was done using a bubble study, while chest X-ray was used for radiographic confirmation. Sensitivity, specificity, predictive values, interrater reliability, and percent agreement between the two methods were assessed. The mean confirmation times were also compared. Results Ultrasound showed 91.6% sensitivity, 96.91% specificity, 78.57% positive predictive value, and 98.95% negative predictive value. Interrater reliability (k = 0.82) and percent agreement (96.3%) were high. Ultrasound confirmed placement 88.29 minutes earlier than chest X-ray. Conclusion Ultrasound confirmation using a saline flush method is accurate and significantly faster than chest radiography for CVC tip verification.